2015
DOI: 10.1177/1049731515574346
|View full text |Cite
|
Sign up to set email alerts
|

Abuses and Mysteries at the Association of Social Work Boards

Abstract: Under contract with the Association of Social Work Boards (ASWB), Pearson VUE reportedly performs much of the work of developing and administering the social work licensing exams required by most states. ASWB charges substantial fees for such exams and, after paying Pearson, has been able to bank considerable sums. One of the key contributions to the arrangement of ASWB is its supply of draft exam questions -which, after statistical pretesting by Pearson, may ultimately appear on licensing exams. Prior researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The licensing pass rate was 77.6% ( n = 250) at the Associate degree level; 68.5% at the bachelor’s level ( n = 2696); 75.4% at the master’s level ( n = 16,698); 64.2% at the advanced general level ( n = 134); and 74.8% at the clinical level ( n = 16,776) (Association of Social Work Boards, 2021c). Other than these general statistics, it is unknown if license pass rates vary by race/ethnicity because the ASWB did not make the detailed pass rates available by demographic groups including race/ethnicity (Woodcock, 2016). Based on the finding of this study, for the master’s social workers, much of the racial disparities are explained by greater structural factors included in the regression analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The licensing pass rate was 77.6% ( n = 250) at the Associate degree level; 68.5% at the bachelor’s level ( n = 2696); 75.4% at the master’s level ( n = 16,698); 64.2% at the advanced general level ( n = 134); and 74.8% at the clinical level ( n = 16,776) (Association of Social Work Boards, 2021c). Other than these general statistics, it is unknown if license pass rates vary by race/ethnicity because the ASWB did not make the detailed pass rates available by demographic groups including race/ethnicity (Woodcock, 2016). Based on the finding of this study, for the master’s social workers, much of the racial disparities are explained by greater structural factors included in the regression analysis.…”
Section: Resultsmentioning
confidence: 99%
“…While Borenzweig indicated that 60% of his sample were white women, the number of people of color and how ethnicity was defined were not presented. In the late 1990s and again in 2008, California would go on to reject ASWB's clinical social work exam citing concerns with representativeness and validity of the exam (Alexander & Johnston, 2008;Woodcock, 2016). They did eventually start requiring the ASWB exam in 2016, which according to Woodcock (2016), had more to do with budget restraints than any changes to the fairness of the exam for California's BIPOC test-takers.…”
Section: Lack Of Data Transparencymentioning
confidence: 99%
“…There are several harsh criticisms of ASWB's clinical exam as being racially biased (Albright & Thyer, 2010;Castex, Senreich, Phillips, Miller, & Mazza, 2019;Woodcock, 2016). However, more introspection is required.…”
Section: Aswb and Racial Test Biasmentioning
confidence: 99%